Biomechanical behavior of endodontically treated premolars using different preparation designs and CAD/CAM materials - Pedrollo Lise, Diogo (2017)
Objectives To evaluate the effect of restoration design (‘2.5-mm deep endocrown’, ‘5-mm deep endocrown’ or ‘5-mm deep post&crown’) and CAD/CAM material type (composite or lithium disilicate glass-ceramic) on the load-to-failure of endodontically treated premolars in absence of any ferrule. Methods The crowns of 48 single-rooted premolars were cut and the roots were endodontically treated. Teeth were randomly divided into six groups (n = 8); teeth in each group were restored using one of the two tested materials with standardized CAD/CAM fabricated endocrowns (with either 2.5-mm or 5-mm deep intra-radicular extension) or conventional crowns (5-mm deep post&crown). After cementation using luting composite, the specimens were immersed in distilled water and subjected to 1,200,000 chewing cycles with a load of 50 N applied parallel to the long axis of the tooth (0°). After cyclic loading, a compressive load was applied at 45° to the tooth's long axis using a universal testing machine until failure. Load-to-failure was recorded (N) and the specimens were examined under a stereomicroscope with 3.5x magnification to determine the mode of failure. Results All specimens survived the 1,200,000 chewing cycles. A significant interaction between restoration design and CAD/CAM material was found using two-way ANOVA. In the ‘2.5-mm deep endocrown’ groups, the composite achieved a significantly higher load-to-failure than the lithium disilicate glass-ceramic, while no differences between materials were found in the ‘5-mm deep endocrown’ and ‘5-mm deep post&crown’ groups. More unfavorable failures (root fractures) were observed for higher load-to-failure values. Conclusions Only following a ‘2.5-mm deep endocrown’ design, composite appeared more favorable than lithium disilicate glass-ceramic as crown material; this may be explained by their difference in elastic modulus. Clinical significance Shallow endocrown preparations on premolars present less surface for adhesive luting and a difference in crown material becomes apparent in terms of load-to-failure. The use of a more flexible composite crown material appeared then a better option.